Chemical exchange rotation transfer imaging of intermediate‐exchanging amines at 2 ppm. (7th June 2017) - Zu, Zhongliang; Louie, Elizabeth A.; Lin, Eugene C.; Jiang, Xiaoyu; Does, Mark D.; Gore, John C.; Gochberg, Daniel F.
Abstract : Chemical exchange saturation transfer (CEST) imaging of amine protons exchanging at intermediate rates and whose chemical shift is around 2 ppm may provide a means of mapping creatine. However, the quantification of this effect may be compromised by the influence of overlapping CEST signals from fast‐exchanging amines and hydroxyls. We aimed to investigate the exchange rate filtering effect of a variation of CEST, named chemical exchange rotation transfer (CERT), as a means of isolating creatine contributions at around 2 ppm from other overlapping signals. Simulations were performed to study the filtering effects of CERT for the selection of transfer effects from protons of specific exchange rates. Control samples containing the main metabolites in brain, bovine serum albumin (BSA) and egg white albumen (EWA) at their physiological concentrations and pH were used to study the ability of CERT to isolate molecules with amines at 2 ppm that exchange at intermediate rates, and corresponding methods were used for in vivo rat brain imaging. Simulations showed that exchange rate filtering can be combined with conventional filtering based on chemical shift. Studies on samples showed that signal contributions from creatine can be separated from those of other metabolites using this combined filter, but contributions from protein amines may still be significant. This exchange filtering can also be used for in vivo imaging. CERT provides more specific quantification of amines at 2 ppm that exchange at intermediate rates compared with conventional CEST imaging. Abstract : Chemical exchange saturation transfer (CEST) imaging of intermediate‐exchanging amine at 2 ppm may provide a means of mapping creatine. However, the quantification of this effect may be compromised by the influence of overlapping CEST signals from fast‐exchanging amines and hydroxyls. We developed an exchange filter effect, named AREXdouble, cpw, to isolate creatine contributions at 2 ppm from other overlapping signals.